Emotion and Religious Practices - Latifa, Rena; Najib, Ala’i; Nurhayati, Siti Rohmah; M. Robbani, Taqiyudin M. (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2023)
This study aims to identify emotions underlying Muslim religious practices/rituals. The sample used in this study consisted of 310 Indonesian Muslim adults from several large cities in Indonesia, using a purposive sampling technique. Participants completed several psychological measurements regarding (1) types of emotions based on Emmons’ theory and (2) religious rituals and contemplative rituals (MAAS). Data was analysed through descriptive statistics and exploratory factor analysis. The results of this study show that the forms of emotion related to Muslim religious practices are emotions of gratitude, security and fear. Emotions of gratitude underlie fasting, such as Ramadhan fasting and Sunnah fasting, zakat and infaq. The emotion of feeling secure underlies forms of worship that are obligatory, such as Daily Prayer. Last, the form of prayer related to feeling secure is the type of prayer intended to obtain Allah’s protection when humans are experiencing disaster, namely Istisqo prayer, Istikharah prayer, and Eclipse prayer.